Aroma chemistry of African Oryza glaberrima and Oryza sativa rice and their interspecific hybrids. (2nd September 2013) - Cho, Sungeun; Nuijten, Edwin; Shewfelt, Robert L; Kays, Stanley J
Abstract Background To increase rice production in Africa, considerable research has focused on creating interspecific hybrids between African (Oryza glaberrima Steud.) and Asian (O. sativa L.) rice in an attempt to obtain the positive attributes of each in new cultivars. Since flavor is a key criterion in consumer acceptance of rice, as an initial inquiry we characterized and compared the aroma chemistry of selected cultivars of African O. sativa ssp. japonica, O. sativa ssp. indica, O. glaberrima, and their interspecific hybrids grown in West Africa, using gas chromatography–mass spectrometry, gas chromatography–olfactometry and descriptive sensory analysis. Results Of 41 volatiles identified across seven representative rice cultivars grown in West Africa, 3, 5, 5‐trimethyl‐2‐cyclopenten‐1‐one, styrene, eucalyptol, linalool, myrtenal and l‐α‐terpineol had not been previously reported in rice. Thirty‐three odor‐active compounds were characterized. 4‐Ethylphenol and (E, E)‐2, 4‐heptadienal were unique to O. glaberrima, and pyridine, eucalyptol and myrtenal were described only in an interspecific hybrid. Descriptive sensory analysis indicated 'cooked grain', 'barny' and 'earthy' attributes were statistically different among the cultivars. Conclusion The aroma chemistry data suggest that it should be possible to separate African cultivars into distinct flavor types thereby facilitating selection of new cultivars with superior flavor in African rice breeding programs. © 2013 Society of Chemical Industry